Application value of nucleic acid MALDI-TOF MS in mycobacterial species identification and drug resistance detection in Mycobacterium tuberculosis - Xiaofang Liu; Honghong Niu; Donglin Guo; Huixia Gao; Lihong Wu; Jingyang Liu; Chunfeng Bai; Yuxi Li; Peilong Wang; Zhengfeng Zhou; Yuling Wang; Jianqin Liang; et al. (Microbiology Spectrum)
ABSTRACT Tuberculosis (TB) and non-tuberculous mycobacteria (NTM) infections pose global health threats, requiring swift and accurate identification for effective treatment. This study aims to assess the ability of nucleic acid matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) to rapidly identify Mycobacterium tuberculosis (MTB), NTM, and the drug resistance of MTB. A comparative analysis of 133 clinical samples was performed using acid-fast bacilli (AFB) staining, Lowenstein–Jensen (LJ) culture, GeneXpert, real-time PCR, and nucleic acid MALDI-TOF MS. The study focused on the diagnostic performance of nucleic acid MALDI-TOF MS in detecting MTB and NTM, as well as its accuracy in identifying the drug resistance profiles of MTB. The positive detection rate of nucleic acid MALDI-TOF MS for mycobacterium was 84.96%, which was significantly higher than that of AFB staining (29.32%). For NTM, nucleic acid MALDI-TOF MS had 89.29% sensitivity and 97.14% specificity, with an area under the curve (AUC) of 0.932, which was superior to other methods. The nucleic acid MALDI-TOF MS identified 28 NTM species, while real-time PCR identified only 12. Drug resistance detection showed concordance rates of 80% to 95% compared with drug sensitivity tests of LJ culture. Nucleic acid MALDI-TOF identified mutations, like KatG315 AGC-ACC for low-level isoniazid resistance, rpoB 531 TCG-TTG for high-level rifampicin resistance, and the InhA-15 C-T mutations, were also found in six isoniazid resistance cases and prothionamide resistance cases. Nucleic acid MALDI-TOF MS is a valuable diagnostic tool for the rapid and precise identification of mycobacterial species and the drug resistance profiles of MTB. With high sensitivity and specificity, it can guide the early initiation of effective anti-tuberculosis treatment in clinical settings.IMPORTANCETuberculosis (TB) remains a critical global health challenge, exacerbated by the emergence of drug-resistant strains. Accurate, rapid diagnosis is imperative for effective treatment and control of TB. The ability to discern MTB from NTM is equally vital, as they demand distinct therapeutic approaches. This study underscores the significance of nucleic acid matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) technology in providing a swift and precise diagnostic tool. Its high sensitivity and specificity in identifying mycobacterial species and their resistance profiles are paramount for guiding targeted anti-tuberculosis therapy. By potentially reducing the time to diagnosis and enabling personalized treatment plans, this technology could revolutionize TB management, ultimately mitigating its impact on public health.